Compensation pathways for venous drainage of the brain in superior sagittal sinus occlusion by parasagittal meningioma - A.H. Sirko; L.A. Dziak; V.A. Perepelytsia; Yu.V. Cherednychenko (Medičnì Perspektivi, 2022)
This study aims to determine the existing pathways of collateral cerebral circulation in parasagittal meningiomas that cause superior sagittal sinus occlusion based on literature review and analysis of own clinical observations. Results of clinical and instrumental examination of 221 patients treated in Dnipropetrovsk Regional Clinical Hospital named after I.I. Mechnikov from 2000 to 2021 were subjected to retrospective and prospective analysis. Inclusion criteria were: patient age of 18+, parasagittal extracerebral tumor according to computed tomography/magnetic resonance imaging, histologically verified meningioma, superior sagittal sinus occlusion (type V-VI according to M.P. Sindou and J.E. Alvernia) according to selective cerebral angiography. This study is based on the analysis of examination of 43 patients who met the inclusion criteria. The selected patients were analyzed for demography (sex, age), brain computed tomography/magnetic resonance imaging before and after intravenous contrast enhancement, and computed tomography angiography and selective cerebral angiography data. Transformed venous drainage pathways were analyzed depending on the location of superior sagittal sinus occlusion by parasagittal meningioma: anterior, middle, or posterior third of the superior sagittal sinus. It was determined that preoperative diagnosis of parasagittal meningiomas that, based on brain computed tomography/magnetic resonance imaging, has signs of type V or VI superior sagittal sinus invasion according M.P. Sindou and J.E. Alvernia, must include selective cerebral angiography. Dynamic images of selective cerebral angiography in the venous phase allows to fully assess the established pathways of collateral blood flow and the blood flow direction. Information on collateral venous circulation in case of superior sagittal sinus occlusion by parasagittal meningioma is extremely important in a surgery planning. It helps avoiding iatrogenic damage to eloquent veins, which increases radical tumor removal with maintaining/improving a patient’s functional state in the early postoperative period and improving long-term treatment outcomes.